Boron/Nitrogen/Oxygen Co-Doped Carbon with High Volumetric Performance for Aqueous Symmetric Supercapacitors. Issue 5 (1st January 2018) - Wang, Chenlong; Zhang, Xugang; Wang, Jinshuang; Ma, Yongjun; Lv, Shixian; Xiang, Junyu; Chu, Mingna; Sun, Ting; Qin, Chuanli
Abstract : From the practical application of supercapacitors, the development of carbon materials with high volumetric performance is highly desired. We report the synthesis of B/N/O co-doped carbon by a facile one-step carbonization method of polyvinylpyrrolidone/melamine formaldehyde resin with boric acid/urea treatment and a subsequent washing process. It is shown that a boric acid/urea treatment is an effective approach to incorporating B into N/O enriched carbon and effectively restraining the generation of inert B-O and B-N species. Moreover, a boric acid/urea treatment and washing process can increase specific surface area, optimize pore structure, and retain many active heteroatoms without lowering density, contributing to good conductivity, fast charge transfer and electrolyte ion diffusion, and high volumetric performance. The fabricated B/N/O co-doped carbon shows high active heteroatoms of 8.69 at.% (N-5, N-6, B-C and O-I), moderate surface area, and pore volume (778.02 m 2 g −1 and 0.341 cm 3 g −1 ), high density (1.3 g cm −3 ), high specific volumetric, and gravimetric capacitances (309 F cm −3 and 238 F g −1 at 0.5 A g −1 ) and superior cycling stability. The assembled symmetric supercapacitor delivers relatively high volumetric energy density (11.5 Wh L −1 at 622 W L −1 ) in 6 M KOH electrolyte. The B/N/O co-doped carbon has great potential for applications in supercapacitors.